META-ANALISIS PENGGUNAAN VIDEO YOUTUBE DALAM PEMBELAJARAN DI ERA NEW NORMAL PADA SISWA SEKOLAH DASAR - Irmatun Nadhifah; Meirza Nanda Faradita; Fitroh Setyo Putro Pribowo (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2021)
The means used as one of the appropriate learning media and helping students learn while learning from home are learning videos via YouTube. Based on the conditions that occurred during the pandemic as well as the study of some of the above theories, the aim of this study was to analyze the use of YouTube videos in elementary school level learning and to find out an increase in learning outcomes and student learning motivation obtained when using YouTube videos in learning. The research used in this research is a type of qualitative research using the meta-analysis method to analyze the relevant research results. The collection of data obtained in this study is done by browsing the journals available in electronic media (internet) that are relevant according to the research title. analysis of the relevant data that has been presented above, it is known that the use of youtube can improve student learning outcomes. Evidenced by the results of the analysis literature reviews with an average value of 83.59.